Lead Phyto extraction in the Huachipa Zoological Park through the use of Tagetes erecta associated with a mycorrhiza and EDTA - Carrera, O. (2020)
Phytoremediation is a potentially less costly approach to treat contaminated soil. Here, the phytoremediation capacity of marigold (Tagetes erecta) in conjunction with EDTA and mycorrhizae was analyzed. Specifically, the ability of the marigold to extract lead from contaminated soils in the Bird Forest Zone of the Huachipa Zoological Park (PZH) was evaluated. Marigold was planted in main areas of interest within the PZH. Plants were treated with different concentrations of mycorrhizae (0 and 0.5 g/kg) and EDTA (0, 0.5 and 1 mg/kg) and later analyzed by atomic absorption spectrophotometry for lead concentrations in the aerial parts and roots of the plants at the end of the experiment. We show that marigold has the ability to extract lead; and under the conditions of the experiment, mycorrhizae did not improve the extraction efficiency. However, EDTA did increase the amount of lead extracted, thus affecting the physiological development of the plant.